Using design thinking in policy practice to revitalize collaboration and solve wicked problems - Lisa Källström; Christine E. Laustsen; Albert Westergren; Maria Haak (Policy Design and Practice, 2025)
Design Thinking (DT) is useful for exploring complex problems and is a promising approach for innovation within policymaking. Still, what design-oriented approaches can mean for the public sector, and how they practically can be implemented in these contexts needs further research. The objective of this study is to unpack how a DT-inspired workshop, aiming at establishing a new policy for intra-organizational collaboration, unfolds in a local government setting. By exploring both the workshop’s implementation and the participants’ experiences, this study offers new insights into the use of design methods in policy design and implementation. Observations, a qualitative questionnaire, and focus groups were used to explore participants’ experiences. The workshop contained three stages: the problem, the solution, and the pitch, characterized by iteration and divergent and convergent thinking. The workshop helped revitalize collaboration within the local government and supported the implementation of the new policy. The DT methodology was perceived not only as structured and goal-oriented, but also a relational, inclusive and knowledge-building process. These five processes occurred simultaneously and were intertwined and illustrates key characteristics of the DT practice.